The CARE Inventory: A Self-Reflective, Behavior-Based Instrument to Guide Professional Development and Mentorship of Academic Faculty - Karyn L. Wulf; Larry Hurtubise; Heather Brod; Philip F. Binkley (Association of American Medical Colleges, 2018)
Introduction Traditional needs assessments often rely on self-reported skill levels. To gather more objective and growth-focused data, we developed a behavior-based inventory to measure perceived faculty competence and desired areas for growth in four common domains of academic medicine: clinical, administrative/leadership, research, and education (CARE). Methods Competencies in teaching, research, and professional development and leadership noted in the literature were used as the foundation of our instrument. Clinical service topics were added, and questions were vetted with the executive committee of our faculty development center. A behavior-based inventory was developed to enhance self-reporting of competency. The instrument was piloted with faculty at an external institution and revisions made prior to data collection. Results In May 2016, the CARE Inventory was sent to all full-time faculty members in the Ohio State University College of Medicine (n = ∼1,800). We received 350 responses (20% response rate). Individual reports were generated and sent to the faculty member and his/her identified mentor for individual professional development. Summary data were used in aggregate for professional development program planning. Discussion Anchoring measurement to current and desired future behavior allows for more self-reflective and growth-oriented assessment for individuals, and results can inform tactical faculty development by both individual and program. We believe this is a scalable and generalizable instrument other academic medical and health sciences programs could use both as a needs assessment tool for program planning and for individualized development plans with faculty and their mentors.